PP13 Improvements in process and intermediate (proxy) outcomes associated with peer led and resourced primary care of patients with type 2 diabetes in Southern Ireland. (2nd September 2014) - Moran, J; Flannery, CM; Quinlan, D; Bradley, C; Murphy, K
Abstract : Background: The Diabetes in General Practice group (DiGP) is an exclusively primary based peer led initiative, involving 46 Republic of Ireland General Practices and their medical and nursing staff. Its genesis arose from difficulties encountered by general practitioners accessing local secondary care services for patients with diabetes. It strives to improve the quality of care for patients with diabetes in their practices through peer support, education, and engagement in audit and feedback. The study reports on the performance of the group over the course of four audits between 2004 and 2010. The standards of care was benchmarked against Irish College of General Practitioners (ICGP) guidelines (2008), an audit Midland Diabetes Structured Care Programme (2008) (another Irish primary care diabetes initiative); and Primary Care Trust data from the 2007/2008 National Diabetes Audit for England and Wales. Methods: Data regarding demographic and clinical variables on patients with Type 2 diabetes were collected from participating general practices in 2004, 2005, 2008 and 2010. These reflected key process of care and intermediate (proxy) outcome indicators. The numbers of patients included in the audit in the respective years were: 487 in 2004; 776 in 2005; 1300 in 2008 and 3129 in 2010. Descriptive analysis of the numbers, percentage, medians, means standard deviations and interquartile ranges of various clinical parameters were used to synopsize the data to facilitate comparisons with reports from other diabetes initiatives. Results: The number of variables captured has expanded greatly since the first audit in 2004. The recording of process of care measures (HbA1c, blood pressure (BP), Cholesterol, Smoking Status, Albumin Creatinine, Ratio, body mass index, foot examination, retinopathy screening) has improved in each successive audit. In 2010, HbA1c, BP and Cholesterol were recorded for more than 85% of patients with type 2 diabetes. Also in 2010, the proportion of type 2 diabetes patients reaching guideline target levels: HbA1c <6.5%, BP <130/80, Cholesterol <4.5 has improved in DiGP practices and compares favourably to national and international audits. Conclusion: A motivated and organised group of general practitioners is achieving a quality of care comparable to national as well as and international standards without specific secondary care or specialist input or leadership. This model of care promotes a pragmatic and efficient use of available primary care resources.